Assessment of aortic stenosis by three-dimensional echocardiography: an accurate and novel approach. Issue 7 (8th May 2007) - Goland, Sorel; Trento, Alfredo; Iida, Kiyoshi; Czer, Lawrence S C; De Robertis, Michele; Naqvi, Tasneem Z; Tolstrup, Kirsten; Akima, Takashi; Luo, Huai; Siegel, Robert J
Abstract : Background: Accurate assessment of aortic valve area (AVA) is important for clinical decision-making in patients with aortic valve stenosis (AS). The role of three-dimensional echocardiography (3D) in the quantitative assessment of AS has not been evaluated so far. Objectives: To evaluate the reproducibility and accuracy of real-time three-dimensional echocardiography (RT3D) and 3D-guided two-dimensional planimetry (3D/2D) for assessment of AS, and compare these results with those of standard echocardiography and cardiac catheterisation (Cath). Methods: AVA was estimated by transthoracic echo-Doppler (TTE) and by direct planimetry using transoesophageal echocardiography (TEE) as well as RT3D and 3D/2D. 15 patients underwent assessment of AS by Cath. Results: 33 patients with AS were studied (20 men, mean (SD) age 70 (14) years). Bland–Altman analysis showed good agreement and small absolute differences in AVA between all planimetric methods (RT3D vs 3D/2D: −0.01 (0.15) cm 2 ; 3D/2D vs TEE: 0.05 (0.22) cm 2 ; RT3D vs TEE: 0.06 (0.26) cm 2 ). The agreement between AVA assessment by 2D–TTE and planimetry was −0.01 (0.20) cm 2 for 3D/2D; 0.00 (0.15) cm 2 for RT3D; and −0.05 (0.30) cm 2 for TEE. Correlation coefficient r for AVA assessment between each of 3D/2D, RT3D, TEE planimetry and Cath was 0.81, 0.86 and 0.71, respectively. The intraobserver variability was similar for all methods, but interobserver variability was better for 3D techniques than for TEE (p<0.05). Conclusions: The 3D echo methods for planimetry of the AVA showed good agreement with the standard TEE technique and flow-derived methods. Compared with AV planimetry by TEE, both 3D methods were at least as good as TEE and had better reproducibility. 3D aortic valve planimetry is a novel non-invasive technique, which provides an accurate and reliable quantitative assessment of AS.